Protein, Lactate Dehydrogenase and Glucose Estimation in Pleural Fluid of Tuberculosis Pleural Effusion Patients - A. M. Siddiqui, Anjali Pergulwar, Amol Shinde, H. N. Khan (International Journal of Innovative Research in Medical Science, 2016)
Introduction: Tuberculosis Pleural effusion is a leading inflammatory pleural disease in clinical practice and a common public health problem related to tuberculosis. Aim: To estimate value of protein, lactate dehydrogenase and glucose, in pleural fluid of tuberculosis pleural effusion patients. Methods and Material: Biochemical tests protein, lactate dehydrogenase and glucose was done in 30 patients of tuberculosis pleural effusion. Result: In our study, mean ± S.D of protein is 5.3 ± 1.4, lactate dehydrogenase is 1007.2 ± 167.6 and glucose is 39 ± 4.8. It shows that protein and Lactate dehydrogenase level is high, when compared with Light’s criteria and glucose level is low. Conclusion: This study concludes that, in tuberculosis pleural effusion patients, pleural fluid shows, high protein, high lactate dehydrogenase, and low glucose level, Hence it is exudative type.